The role of industrial social workers in integrating people with physical challenges in the work place (2017)
There is a misconception and belief by employers that persons with disabilities can be regular absentees at work, non-productive and not suitable for employment. The result is seeing persons with disabilities that are gainfully employed at workplace as strangers in the foreign land; whereas some of these physically challenged persons may be willing to work efficiently and effectively If given the opportunity to actively participate in the labour force rather than been excluded This study, therefore. examined job commitment adequacy of job performance, and/or otherwise of absenteeism of persons with disabilities from the point of view of employers and supervisors to whom they are responsible. The descriptive survey research design of the ex-post facto type was used for the study. The population consists of all employees in the selected workplaces in Oyo State/ Nigeria namely: Oyo State Civil Service, Federal Secretariat Ibadan, University of Ibadan and Federal College of Education (Special/ Oyo. The staff of the establishments were clustered into the able-bodied and the physically-challenged The total number of the physically challenged from the four establishments was 175 and a random sampling technique was used to select 275 non-physically challenged employees from where a physically challenged person is selected The supervisors of chosen samples (75 in number) were then contacted to respond to the questionnaires that elicit information about the 450 employees. A questionnaire tagged. "Employees Workplace Performance/Commitment and Attendance Questionnaire" at 0.05 level of significance was utilized to elicit response. The findings showed there is no significant difference in the work performance/ job commitment and absentee rates of physically challenged people and those that are non-physically challenged in the workplace. Based on these findings and for full integration of persons with disabilities into the workplace/ employers/ through their services and involvement of industrial social workers/ should work on job designs, access to the workplace/ work area design and give proper training and orientation to both the disabled and non-disabled persons at the workplace. Also/ there is the need to put in place flexible workplace practices that are peculiar and advantageous to the persons with disabilities. Full integration of physically challenged into the workplace will not only reduce the cost of maintenance by the family and society but will also reduce the poverty within the economy.